Wykorzystanie podejścia procesowego we wdrażaniu outsourcingu - Międła, Katarzyna (A Process Approach in the Implementation of Outsourcing, 2009)
The outsourcing is a very popular concept applied in order to reorganize a company and to make it more flexible and adaptable. However, the outsourcing is a complicated instrument. Its success depends on many factors. Most often the failures of outsourcing's implementation occur due to mistakes made during the introductory stage. The aim of this article is to introduce the reader to the issue of using the process approach in a correct outsourcing's implementation. The work is of theoretical-empirical character. In the article, the idiographic approach is used. The searching techniques used by the author are the analysis of the sources, the interview, and the observation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 81-89